2015
DOI: 10.1016/j.jclepro.2014.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable universities – a study of critical success factors for participatory approaches

Abstract: Participatory approaches can be seen as a requirement, but also as a benefit to the overall paradigm change towards sustainable development and contribute towards the integration of sustainability concept into the university culture. So far, there have been comparatively few research studies on participation within sustainability implementation at university level, and a more differentiated understanding of these processes is still missing, both in the practice of conducting a participatory process and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
177
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(198 citation statements)
references
References 51 publications
7
177
0
14
Order By: Relevance
“…In these hierarchical environments, participatory processes are clearly positive in order to meet social demands. In literature, a growing number of studies focus on the benefits of participatory approaches in HEIs to contribute towards the integration of sustainability in their missions, values and activities and tools that encourage an effective participatory stakeholder engagement (Reed et al 2009;Disterheft et al, 2015a;Disterheft et al, 2015b;Disterheft et al, 2016).…”
Section: Stakeholder Engagement In Heismentioning
confidence: 99%
“…In these hierarchical environments, participatory processes are clearly positive in order to meet social demands. In literature, a growing number of studies focus on the benefits of participatory approaches in HEIs to contribute towards the integration of sustainability in their missions, values and activities and tools that encourage an effective participatory stakeholder engagement (Reed et al 2009;Disterheft et al, 2015a;Disterheft et al, 2015b;Disterheft et al, 2016).…”
Section: Stakeholder Engagement In Heismentioning
confidence: 99%
“…Participation is also explored in the HESD context, as [12] (p. 1) mention, becoming a request to achieve sustainable development in HEI, and it "contributes towards the integration of sustainability concept into the university culture." Hence, co-creation, co-design and co-production of sustainability in higher education is possible to achieve through the engagement of the stakeholders involved, and specially, students.…”
Section: The Relationship Between Participation and Co-creationmentioning
confidence: 99%
“…It has been shown that students, as one of the key stakeholders in university processes, need to be empowered to implement successfully SD in HE [12]. Also, it has been identified some strategic fields to redirected the organizational change for HESD, been among them "institutional commitment, shared vision of the future, sustainability indicator reporting, participatory management structures and external partnerships" [72] (p. 700); consequently, the participatory approach constitutes a key element.…”
Section: The Relationship Between Participation and Co-creationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (Church et al, 2012), the results provide support for integrating trait and cultural psychology perspectives, as well as structure and process approaches, in the study of self-concepts across cultures. Disterheft et al (2015) mentioned the success of participatory approaches is interdependent with structural institutional conditions and the persons engaged, highlighting the importance of specific skills and participatory competencies. A better integration of the dimensions of participation into sustainability assessment practices can help in defining and establishing participatory approaches on institutional level and fostering a culture of participation in the transition to sustainable universities.…”
Section: Introductionmentioning
confidence: 99%